Strategi Penghimpunan Dan Penyaluran Zakat, Infaq, Shadaqah Pada Lembaga Amil Zakat Infaq Shadaqah Muhammadiyah (LAZISMU) Kota Medan - Aswin Fahmi D (Universitas Islam Negeri Sumatera Utara, 2019)
Management of ZIS in the city of Medan has entered a modernization era where zakat management is directed to amil zakat institutions that specifically deal with the ZIS problem. Now there are many LAZ in Medan, including LAZISMU. Both LAZISMU have enormous potential, because they are under the auspices of the largest Islamic organization in Indonesia. However, in the funding and distribution activities of ZIS in LAZISMU, there is still no promising performance. Some notes show that the number of ZIS that have been funded by these two LAZIS is still relatively low. And the distribution of ZIS has not yet shown maximum results. The research is a field research, namely research conducted or conducted in a specific place using descriptive analysis methods. Descriptive analysis is research that describes clearly and in detail the phenomena that are the subject matter without hypothesizing or doing statistical calculations, which in this case describes clearly and in detail about the main problems that occur in the ZIS collection and utilization strategy in LAZISMU City Field. The results of this study can be concluded that LAZISMU uses its strategic position and utilizes technological advancements to improve the performance of ZIS collection and distribution.